Manhunt : the twelve-day chase for Lincoln's killer - Swanson, James L., 1959- (Harper Perennial, 2007)
Recounts the escape of John Wilkes Booth, Abraham Lincoln's assassin, and follows the intensive search for him from the streets of Washington, D.C., through the swamps of Maryland, into the forests of Virginia.